Green Approach for Fabrication and Applications of Zinc Oxide Nanoparticles - Brajesh Kumar; Kumari Smita; Luis Cumbal; Alexis Debut (Bioinorganic Chemistry and Applications)
Zinc oxide nanoparticles (ZnO-NPs) are known to be one of the multifunctional inorganic compounds which are widely used in everyday applications. This study aims to fabricate ZnO-NPs using grapefruit (Citrus paradisi) peel extract with particle size ranging from 12 to 72 nm. Structural, morphological, and optical properties of the synthesized nanoparticles have been characterized by using UV-Vis spectrophotometer, TEM, DLS, and FTIR analysis. They show the significant photocatalytic degradation efficiency (>56%, 10 mg/L, 6 h) against methylene blue and antioxidant efficacy (≥80% for 1.2 mM) against 1,1-diphenyl-2-picrylhydrazyl. From the results obtained it is suggested that green ZnO-NPs could be used effectively in environmental safety applications and also can address future medical concerns.